2017
DOI: 10.1111/apa.13826
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and antimicrobial protein and peptide levels in preterm infants

Abstract: Aim: To characterise the secreted and inducible antimicrobial protein and peptide (APP) levels in a prospective cohort of preterm infants (<30 weeks gestational age) with or without Bifidobacterium breve M16V supplementation during the first month of life. Methods:We analysed serial biosamples of infants who did (n = 13) or did not receive (n = 62) B. breve (3 9 10 9 cfu/day). Peripheral blood was obtained on days 1, 14 and 28, and infant stool prior to commencement of probiotic supplementation and on day 21. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…An aliquot of MEE was thawed and used to quantify the following AMPs: Human beta defensin 1 (HBD1), Human beta defensin 2 (HBD2), LL-37, lactoferrin, bactericidal/permeability-increasing protein (BPI) and secreted phospholipase A 2 (sPLA 2 ). HBD1, HBD2, LL-37 and lactoferrin levels were measured using in-house multiplex fluorescent bead-based assays on the Bio-Plex® 200 system (Bio-Rad Laboratories, California, USA) [30]. BPI and sPLA 2 levels were measured using commercial ELISA kits (Hycult Biotech, Plymouth Meeting, PA, USA, and Cayman Chemical, Ann Arbor, MI, USA, respectively) and according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…An aliquot of MEE was thawed and used to quantify the following AMPs: Human beta defensin 1 (HBD1), Human beta defensin 2 (HBD2), LL-37, lactoferrin, bactericidal/permeability-increasing protein (BPI) and secreted phospholipase A 2 (sPLA 2 ). HBD1, HBD2, LL-37 and lactoferrin levels were measured using in-house multiplex fluorescent bead-based assays on the Bio-Plex® 200 system (Bio-Rad Laboratories, California, USA) [30]. BPI and sPLA 2 levels were measured using commercial ELISA kits (Hycult Biotech, Plymouth Meeting, PA, USA, and Cayman Chemical, Ann Arbor, MI, USA, respectively) and according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Studies comparing talactoferrin and bLF remain to be done. Given the common use of probiotics, potential interactions between oral probiotics and bLF/talactoferrin should be tested ( 171 ).…”
Section: Current Interventions With Clinical Evidence Of Benefitmentioning
confidence: 99%
“…Readers may also be interested in the paper by Strunk et al. who found that antimicrobial protein and peptide levels were not altered in very preterm infants by Bifidobacterium breve supplements. The findings are discussed in the accompanying editorial by Popescu et al.…”
Section: Probiotics May Prevent Necrotising Enterocolitis In Preterm mentioning
confidence: 99%